Variable clinic-EEG trajectories in male patients with PCDH19 clustering epilepsy - D. V. Dmitrenko; A. А. Sharkov; E. А. Domoratskaya; A. А. Usoltseva; I. V. Volkov; D. V. Pyankov (Эпилепсия и пароксизмальные состояния, 2023)
Background. The association between the protocadherin-19 (PCDH19) gene and epilepsy suggests that the X-linked inherited form of its pathogenic variant affects only women. Recent data has described males with somatic mosaicism, whose clinical picture is similar to the common manifestations in females.Objective: to report on three new cases of PCDH19 clustering epilepsy in male patients.Material and methods. Clinical data were collected from different centers through personal communication between authors, which means that the structured cohort was not tested. For all patients a next generation sequencing-based custom epilepsy gene panel and whole-exome sequencing by NextSeq 500 (Illumina Inc., USA) were performed.Results. All patients had a previously described mosaic variants in PCDH19 gene (NM_001184880.1). According to the electroencefalographic data, all patients had a diffuse slowdown of the background rhythm, interictal regional/multiregional epileptiform activity and ictal focal pattern in the frontotemporal regions. Brain magnetic resonance imaging at the age of 3 years showed delayed myelination without focal abnormalities in 2 patients.Conclusion. Early recognition of the above features should improve early diagnosis and long-term management of patients with epilepsy and PCDH19 mutations.